O “mito” do desenvolvimento rural da microrregião de Toledo no Oeste do Paraná - Dias , Luiz Carlos (2022)
This research study aims to analyze the extent to which the transformations that have occurred in the agricultural production structure of the Toledo Microregion, in western Paraná, provided a local rural development process. This region was directly benefited by government policies, which began in the 1950s with the technological package instituted and encouraged by the Federal Government, which benefited, above all, cultures destined for the external market. In this context, the region has achieved significant importance in terms of production and productivity of the agricultural and cattle-raising sector in the state and national scenario, based on the production of soybean and corn commodities, pig and poultry raising, and the transformations that derive from this productive agenda. The research problem that guides this study questions the process of economic growth of agriculture and cattle- raising in the Microregion of Toledo as capable of generating development. Thus, the objective is to clarify the adopted productive model and analyze the factors that are contributing to or inhibiting local development. Based on Celso Furtado's theory, the distinction between the process of economic growth and development was analyzed, as well as, through institutional theory, especially Douglass North's contributions, it was determined how the laws and customs accompanied by the social organizations of a locality can contribute or inhibit development. The instruments used were based on qualitative and quantitative research and it required a three-way construction: a) understanding the Region's formation from the historical, economic and social aspects that, as a whole, determined the Region's characteristics; b) the endogenous and exogenous factors and their influences on the productive model adopted in regional agriculture and cattle-raising that determined the responses in terms of production and productivity; c) the effects of these options, considered obstacles to the Region's full development. The results obtained highlight that the expressive growth of the Region derived from a productive redirection based on the incentives given by the State, the increase in external demand, and the cultural and historical aspects of the local population. However, the observed growth produced adverse effects on full development. As a highlight, it was mentioned aspects of agricultural and cattle production, such as the productive concentration in soybean, corn, pork, and poultry, and the consequent loss of dynamism of traditional cultures, concentration of land ownership, and exclusion of rural labor; social aspects, such as low levels of education and income of the population; environmental aspects that revealed the extremely poor conservation status of the Region's Hydrographic Basins, pesticide consumption much higher than the state average, high levels of water pollution, and aspects related to the health of the local population, with emphasis on high rates of poisoning, disease, and death caused by pesticides. Thus, based on the results pointed out, the "myth" of the rural development of the Microregion of Toledo becomes evident.